Entrepreneur-Region Fit and Entrepreneurial Success in China: The Effect of “Confucian” Personality - Zhou, Mingjie; Mu, Weiqi; Li, Fugui; Zhou, Yixin; Huang, Duan; Wang, Kexin; Zhang, Jianxin (Frontiers in Psychology, 2021)
The personality of entrepreneurs is associated with their entrepreneurial success, and the regional personality plays a crucial role in the entrepreneurial ecosystem. Recently, scholars have called for an indigenous personality perspective and combining the personality of entrepreneurs with the regional personality. The current study aimed to investigate the indigenous Confucian personality (e.g., interpersonal relatedness [IR]) and taking an entrepreneur-regional personality fit perspective, allowing testing how entrepreneurs interact with the local ecosystem. Using the personality data of entrepreneurs (N = 1,386) from a representative sample across 42 major cities in China, we found that (1) city-level IR is curvilinearly correlated with the annual income of entrepreneurs, with moderate IR associates with the highest income; and (2) the entrepreneur-regional fit analysis further revealed substantial interplay between an entrepreneur and the city. Specifically, entrepreneurs who have moderate IR and run their business in the city also with moderate IR are most likely to have the highest income. This study highlights the usefulness of investigating indigenous personality and the fit perspective in entrepreneurship research.